Transforming Science Learning with Augmented Reality: The Impact of Assemblr Edu on Cognitive Dissonance and Thinking Skills - I Kadek Angga Yatha Wiweka; I Wayan Widiana; Gede Wira Bayu (Universitas Pendidikan Ganesha, 2024)
Third-grade elementary school students often struggle to comprehend the concept of complete metamorphosis, which can trigger cognitive dissonance and hinder the development of complex thinking skills. This study aims to develop an Assemblr Edu-based augmented reality learning media within a metacognitive learning framework to reduce cognitive dissonance and enhance students' complex thinking abilities. The development process follows the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The applied metacognitive strategies encompass planning, monitoring, and evaluating. Data collection methods include questionnaires, essay tests, and interviews with homeroom teachers. Media validity was assessed by four media experts and four subject matter experts, while practicality was evaluated based on responses from 24 third-grade students. The effectiveness of the media was examined using a one-group pretest-posttest design with a sample of 24 students. The data were analyzed using both qualitative and quantitative approaches. The results indicate that Assemblr Edu demonstrates high validity, with scores of 0.94 from media experts and 0.93 from subject matter experts. The practicality assessment yielded a score of 92.88%, categorizing the media as highly effective and practical. Effectiveness testing revealed a significant impact in reducing cognitive dissonance and improving students' complex thinking skills. Thus, this media is effective as a learning aid in metacognitive instruction at the elementary school level.